The role of GnRH metabolite, GnRH-(1-5), in endometrial cancer - Cho-Clark, Madelaine J.; Watkins, Allison; Wu, T. John (Frontiers in Endocrinology, 2023)
From the time of its discovery and isolation in the mammalian hypothalamus, the decapeptide, gonadotropin-releasing hormone (GnRH), has also been found to be expressed in non-hypothalamic tissues and can elicit a diverse array of functions both in the brain and periphery. In cancer, past studies have targeted the gonadotropin-releasing hormone receptors (GnRHR) as a way to treat reproductive cancers due to its anti-tumorigenic effects. On the contrary, its metabolite, GnRH-(1-5), behaves divergently from its parental peptide through putative orphan G-protein coupled receptor (oGPCR), GPR101. In this review, we will focus on the potential roles of GnRH-(1-5) in the periphery with an emphasis on its effects on endometrial cancer progression.